2021
DOI: 10.1371/journal.pone.0248686
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of depressive symptoms during inpatient treatment is not associated with changes in heart rate variability

Abstract: Vagally mediated heart rate variability (HRV) is a psychophysiological indicator of mental and physical health. Limited research suggests there is reduced vagal activity and resulting lower HRV in patients with Major Depressive Disorder (MDD); however little is actually known about the association between HRV and symptoms of depression and whether the association mirrors symptom improvement following psychotherapy. The aim of this study was to investigate the association between antidepressant therapy, symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…The present study goes some length in achieving this, however, future studies should use an intervention design where some participants are trained in explicitly applying the model. While the vagal tone is considered a stable trait that is hard to change with intervention (e.g., Brunoni et al, 2013b ; Wheeler et al, 2014 ; Neyer et al, 2021 ), metacognition is something that can be trained (Jøsok et al, 2016 ; Fleur et al, 2021 ). Thus, it would be both interesting and necessary to assess whether individuals who are trained in applying the OLB model but have low vagal tones perform better than individuals who are not trained in using the model but have high vagal tones.…”
Section: Discussionmentioning
confidence: 99%
“…The present study goes some length in achieving this, however, future studies should use an intervention design where some participants are trained in explicitly applying the model. While the vagal tone is considered a stable trait that is hard to change with intervention (e.g., Brunoni et al, 2013b ; Wheeler et al, 2014 ; Neyer et al, 2021 ), metacognition is something that can be trained (Jøsok et al, 2016 ; Fleur et al, 2021 ). Thus, it would be both interesting and necessary to assess whether individuals who are trained in applying the OLB model but have low vagal tones perform better than individuals who are not trained in using the model but have high vagal tones.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Sarlon et al [ 50 ] found no association between HRV and depressive symptoms severity. Neyer et al [ 49 ] showed in a prospective study with HRV measures before and after treatment that depressive symptoms improved without change in HRV, suggesting a more complex relationship.…”
Section: Resultsmentioning
confidence: 99%
“…While vagal tone is considered a stable trait that is hard to change with intervention (e.g. Brunoni et al, 2013b;Neyer et al, 2021;Wheeler et al, 2014), metacognition is something that can be trained (Fleur et al, 2021;Jøsok et al, 2016). Thus, it would be both interesting and necessary to assess whether individuals who are trained in applying the OLB model but have low vagal tone perform better than individuals who are not trained in using the model but have high vagal tone.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%